The Potential of Clove Rhizospheric Bacteria to Produce Vanillin from Eugenol - Nurfahmi, Riziq Ilham; Mubarik, Nisa Rachmania; Rusmana, Iman; Tambunan, Ika Roostika; Akhdiya, Alina (HAYATI Journal of Biosciences, 2024)
Vanillin is one of the most important flavoring agents worldwide. Currently, consumers' awareness and concern for biovanillin production has been increasing. This study aimed to screen the potential of clove rhizospheric bacteria isolates producing vanillin through a biotransformation process of eugenol and to conduct the preliminary optimization of the biotransformation condition. Twenty-eight bacteria isolates were screened for their capability to transform eugenol into vanillin. BKL 15 isolate, which was identified as Lysinibacillus xylanilyticus, was selected as the highest vanillin producer among the isolates. The optimum molar yield of vanillin produced by the selected isolate was 4.99% (1.11 g/L) after 168 hours of biotransformation process in the medium consisting of TSB (30 g/L), eugenol (24 g/L), yeast extract (20 g/L), and concentration of casamino acid (20 g/L). Throughout the publications we have read, this is the first report of L. xylanolyticus that produces vanillin.